Cellular grafts in management of leucoderma - Mysore Venkataram; Salim T (Wolters Kluwer Medknow Publications, 2009)
Cellular grafting methods constitute important advances in the surgical management of leucoderma. Different methods such as noncultured epidermal suspensions, melanocyte cultures, and melanocyte-keratinocyte cultures have all been shown to be effective. This article reviews these methods.